HUMAN IMMUNE SYSTEM AND PHYSICAL EXERCISE - Z. Ch. Musin; S. V. Latukhov (Медицинская иммунология, 2014)
Abstract. Physiological and biochemical changes proceeding in muscles during physical loads exert systemic influence upon protein biosynthesis. This process is accelerated in presence of free amino acids, sufficient quantities of hormones, creatine, hydrogen ions. High proton concentrations in tissues and longitudinal physical loadings upon human organism suppress the protein biosynthesis, thus leading to decomposition of hormones, immunoglobulins and cell damage. These changes may explain the development of various immunodeficiencies in sportsmen.